Floral micromorphology and anatomy and its systematic application to Neotropical Bulbophyllum section Micranthae (Orchidaceae) - Nunes, Elaine L. P. [UNESP]; Maldonado, Paula Emmerich [UNESP]; Smidt, Eric C.; Stuezel, Thomas; Coan, Alessandra Ike [UNESP] (Oxford Univ Press, 2017)
Bulbophyllum section Micranthae comprises 12 species distributed in Central South America and, according to molecular data, these are divided into three lineages. Bulbophyllum mentosum is sister to the two remaining clades: the first clade comprises two species easily recognized by their cylindrical leaves and purple flowers and the second, Bulbophyllum section Micranthae s.s., comprises species displaying a high degree of vegetative and floral similarity, frustrating delimitation and identification. The floral micromorphological and anatomical features of eight species belonging to this section were analysed using conventional techniques to verify character states of possible phylogenetic value. All the species were homogeneous for 48 characters, the most relevant being sepals with sunken glandular trichomes and a labellum with centrally differentiated areas (adaxial sulcus and abaxial keel). Another 54 characters were variable and allowed not only the characterization of clades, but also the distinction of species, especially of the morphologically and putative closely related Bulbophyllum epiphytum and Bulbophyllum rupicolum, which have different cuticle deposition patterns. From the assessed characters, four showed synapomorphic states supporting the relationship between the two more recently derived clades. We also discuss the position of B. mentosum, which displays strong floral morphoanatomical divergence and many autapomorphic character states.
Keywords: Bulbophyllum epiphytum; Bulbophyllum rupicolum; character evolution; HCA labellum; secretion